The influence of heat treatment on microstructure and phase transformation Temperatures of Cu-Al-Ni shape memory alloy - Ivanić, Ivana, inženjerka metalurgije (Array, 2019)
This paper presents the results of thermal and microstructural analysis of Cu-Al-Ni shape memory alloy before and after heat treatment. After casting, a bar of Cu-12.8 Al-4.1 Ni (wt.%) alloy, obtained by the vertical continuous casting technique, was subjected to a certain heat treatment procedure. Solution annealing was performed at 850 °C for 60 min, followed by water quenching. Tempering was then performed at four different temperatures (150 °C, 200 °C, 250 °C and 300 °C). The microstructural results were obtained by optical and scanning electron microscopy. Thermodynamic calculation of ternary Cu-Al-Ni system under equilibrium was performed using Thermo-Calc 5 software. Phase transformation temperatures were determined by differential scanning calorimetry (DSC). The DSC results show the highest values of transformation temperatures in as-cast state. After solution annealing and tempering, the transformation temperatures show lower values with exceptional stability of Ms temperature (martensite start temperature).